2023
DOI: 10.3390/ijms242015265
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sex and Genetic Variation in Relevant Pharmacogenes on the Pharmacokinetics and Safety of Valsartan, Olmesartan and Hydrochlorothiazide

Paula Soria-Chacartegui,
Pablo Zubiaur,
Dolores Ochoa
et al.

Abstract: Drug combination therapy is the most common pharmacological strategy for hypertension management. No pharmacogenetic biomarkers for guiding hypertension pharmacotherapy are available to date. The study population were 64 volunteers from seven bioequivalence trials investigating formulations with valsartan, olmesartan and/or hydrochlorothiazide. Every volunteer was genotyped for 10 genetic variants in different transporters’ genes. Additionally, valsartan-treated volunteers were genotyped for 29 genetic variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Notably, its association with portal hypertension in liver cirrhosis patients has been elucidated [ 31 ]. In addition, research by Soria-Chacartegui suggested a potential involvement of CYP2D6 in the metabolism of valsartan [ 9 ]. These developments suggest a more complex and nuanced role for CYP2D6 in drug metabolism, particularly concerning ARBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, its association with portal hypertension in liver cirrhosis patients has been elucidated [ 31 ]. In addition, research by Soria-Chacartegui suggested a potential involvement of CYP2D6 in the metabolism of valsartan [ 9 ]. These developments suggest a more complex and nuanced role for CYP2D6 in drug metabolism, particularly concerning ARBs.…”
Section: Discussionmentioning
confidence: 99%
“…This unique domain structure enables the enzyme to oxidize a wide range of pharmaceutical compounds. Responsible for metabolizing nearly a quarter of all clinically used drugs, including adrenergic antagonists [ 7 , 8 ] and ARBs [ 9 ], CYP2D6 exhibits considerable polymorphic diversity. To date, over 172 CYP2D6 gene variants have been identified ( https://www.pharmvar.org/ , last accessed: 11 December 2023), with many of which are linked to reduced enzymatic function, potentially affecting drug efficacy [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%